Deaths in young people after contact with the youth justice system: a retrospective data linkage study - Kinner, Stuart; Tibble, Holly; Hail-Jares, Katie; Borschmann, Rohan; Spittal, Matthew; Clough, Alan; Sawyer, Susan; Miller, Adrian; Cadet-James, Yvonne (International Journal of Population Data Science, 2018)
Introduction Young people who have contact with the youth justice system are distinguished by a high prevalence of complex, co-occurring health problems, including known risk factors for preventable mortality. However, almost nothing is known about health outcomes for these young people after separation from the youth justice system. Objectives and Approach We aimed to examine the incidence, timing, causes and risk factors for death in justice-involved young people. We linked youth justice records in Queensland, Australia 1993-2016 (N=48,963) with adult correctional records and the National Death Index. We split the cohort into three subgroups: those who had ever been in detention (n=7,643), those supervised in the community but never detained (n=12,953), and those charged with an offence but never convicted (n=28,367). We calculated all-cause and cause-specific crude mortality rates (CMRs), and indirectly standardised mortality ratios (SMRs). We used Cox regression to identify static and time-varying risk factors for death. Results During a median of 13.6 years of follow-up there were 1,452 deaths (3.0%). The all-cause CMR was 2.2 (95%CI 2.1-2.3) per 1000 person-years, and the all-cause SMR was 3.1 (95%CI 3.0-3.3). The leading external causes of death were suicide (32% of all deaths), transport accidents (16%), accidental drug-related causes (13%), and violence (3%). In adjusted analyses, independent risk factors for all-cause mortality included being male (HR=1.4, 95%CI 1.2-1.6) and older (>=15 vs. vs. charge only; HR=1.6, 95%CI 1.2-2.0) and subsequent incarceration as an adult (HR=1.8, 95%CI 1.4-2.4). Conclusion/Implications Young people who have contact with the youth justice system are at markedly increased risk of preventable death, after separation from that system. Efforts to improve long-term health outcomes for justice-involved youth have the potential to reduce preventable deaths in these highly vulnerable young people.